Molecular therapy for ectopic pregnancy - Agus Cakhantara; Aditya Prabawa (Department of Anatomy, Medical Faculty, Universitas Udayana, Bali-Indonesia, 2019)
Objective : To compare treatment in ectopic pregnancy within combination gefitinib, methotrexat and methotrexat only Method : Literature Review Result : Ectopic pregnancies are serious condition that can be fatal, therefore the prompt therapeutic is essential. There some recent studies explain molecular target therapeutic use combination of gefitinib and methotrexat is more effective inducing placental cell death and can rapidly resolve tubal ectopic pregnancy than methotrexate only. If a large clinical randomized trial confirm these finding, these combination could become a new medical option for ectopic pregnancy Conclusion : Combination gefitinib and methotrexate is more effective in ectopic pregnancy than methotrexate only